2019
DOI: 10.1001/jamapsychiatry.2018.3652
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Risk Factors for Psychiatric Disorders and Traits of These Disorders in a Swedish Population Twin Sample

Abstract: This study assesses the association of the genetic risk for psychiatric disorders with population traits of these disorders in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 52 publications
4
121
2
Order By: Relevance
“…In this study, we extended previous work by assessing genetic overlap between OCD, OCS in the population, and CNS and peripheral insulin signaling. While previous studies (19, 25) have yielded a shared genetic etiology between OCD and the total population-based OCS score, our analyses using phenotypic and genetic data of 650 children and adolescents from the population (PNC cohort) found genetic sharing between OCD and the OCS factors ‘impairment’, ‘contamination/cleaning’, and ‘guilty taboo thoughts’. We validated the finding for ‘contamination/cleaning’ in the larger Spit for Science cohort (n=5047).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In this study, we extended previous work by assessing genetic overlap between OCD, OCS in the population, and CNS and peripheral insulin signaling. While previous studies (19, 25) have yielded a shared genetic etiology between OCD and the total population-based OCS score, our analyses using phenotypic and genetic data of 650 children and adolescents from the population (PNC cohort) found genetic sharing between OCD and the OCS factors ‘impairment’, ‘contamination/cleaning’, and ‘guilty taboo thoughts’. We validated the finding for ‘contamination/cleaning’ in the larger Spit for Science cohort (n=5047).…”
Section: Discussioncontrasting
confidence: 57%
“…In addition to contributing to overall OCS, genetic factors contribute to specific OCS dimensions, including contamination/cleaning (2123) and checking/ordering (23, 24). Genetic overlap between clinical OCD and OCS in the population is suggested by the fact that polygenic risk scores (PRS) based on OCD GWAS data significantly predict OCS in two population-based samples of 6931 and 3982 individuals, respectively (19, 25).…”
Section: Introductionmentioning
confidence: 99%
“…21 However, previous analyses of BD PGS also found no associations with continuous measures of psychopathology in childhood 32,60 or adolescence. 61 These results may be explained by less powerful BD GWAS compared with MD and other traits, which might result in underpowered PGS. Nevertheless, the lack of association with BD PGS may also suggest that genetic risk for BD does not manifest until later in development, but given the higher prevalence rates of childhood psychopathology in offspring of parents with BD, this seems less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) indicate modest single-nucleotide polymorphism heritability (SNP-h 2 ) for some PENS in mid-adolescence (3%-9%) and for schizotypy in adults (20%-27%) [20][21][22] . Psychotic experiences share genome-wide genetic influences with schizophrenia and major depression 20,[23][24][25][26] , although not all studies found this, particularly those that used comparatively smaller samples or polygenic scores (PGS) from less well-powered GWAS 23,24,[27][28][29][30][31] . Schizophrenia PGS has been associated with schizotypy in adults assessed using semi-structured interviews, but not with self-rated PENS 32 .…”
Section: Introductionmentioning
confidence: 99%